2021
DOI: 10.1002/ldr.4118
|View full text |Cite
|
Sign up to set email alerts
|

Soil recovery of alluvial gold mine spoils in the Peruvian Amazon using Stylosanthes guianensis, a promising cover crop

Abstract: The Amazon is an important reservoir of biodiversity and carbon but it is under pressure by multiple threats such as artisanal and small‐scale gold mining (ASGM). In Peru ASGM has degraded 90,000 ha of old‐growth forest since the eighties, leaving vast areas as wastelands. As most ASGM in the region is illegal, efforts to recover degraded areas have been scant. Here we assessed the potential of Stylosanthes guianensis to recover soil health as a first step in the restoration of gold mine spoils in a Native com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Precisely, soil in humid tropical forests with slightly lower clay content is less probable to encounter physical protection of mineral-associated organic matter, resulting in higher k ref of the fast and slow pools 58 . However, the significantly lower pH (e.g., <5 units) constrains fungal decomposition of chemically-recalcitrant SOM 84 . In the Australian desert areas, the response of k ref to the explanatory factors is contrary to that of the Amazon Rainforest, which is probably because the relatively high pH (e.g., 7−9 units) limits bacterial activities but maximizes fungal energy efficiency 78 , 85 .…”
Section: Discussionmentioning
confidence: 99%
“…Precisely, soil in humid tropical forests with slightly lower clay content is less probable to encounter physical protection of mineral-associated organic matter, resulting in higher k ref of the fast and slow pools 58 . However, the significantly lower pH (e.g., <5 units) constrains fungal decomposition of chemically-recalcitrant SOM 84 . In the Australian desert areas, the response of k ref to the explanatory factors is contrary to that of the Amazon Rainforest, which is probably because the relatively high pH (e.g., 7−9 units) limits bacterial activities but maximizes fungal energy efficiency 78 , 85 .…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that heavy machinery mining may have a considerable negative effect on species diversity [21], because suction pumping mining forest stands harbor on average approximately two times more species than heavy machinery stands. Given that species diversity usually starts near zero with no woody plants, due to the elimination of vegetation cover [39,41,42] and severe soil degradation [20,43,44,54] by goldmining, our results highlight the lower impact of suction pumping mining on landscape structure, which promotes an increase over time as new species become established [79], and facilitates the faster recovery across the landscape [80]. The lower species diversity after mining abandonment may be explained by a higher dominance (IVI > 10, Table 3) or monodominance [30,95] of pioneer species in 0-5-year-old stands, due to higher tolerance of certain species to unfavorable soil conditions [95] generated by goldmining activities in the study area.…”
Section: Recovery Of Agb Tree Diversity and Forest Structurementioning
confidence: 99%
“…In the Southeastern Peruvian Amazon (Madre de Dios), studies on biomass estimates in natural regeneration after abandonment by mining activities are scarce. Most studies have focused on assessing the species diversity, floristic attributes, species composition [20,40,41], reforestation/rehabilitation experiments of these degraded ecosystems [42][43][44][45][46], and monitoring forest loss due to goldmining [19,26]. These studies showed that the degree of resilience of tree communities after abandonment by mining activities depends on the level of landscape fragmentation [41], stand age [20], and distance from the forest edge [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plantings of legumes can improve mine substrates by fixing nitrogen into the soil, and may also serve as a sustained source of organic matter by providing leaf litter (Peláez et al, 2013; Schimann et al, 2012; Thomas, 2014). Established plants also improve soil quality by increasing soil pH, soil organic carbon, available phosphorus, exchangeable potassium (Peláez et al, 2013; Tetteh, Logah, et al, 2015), cation exchange capacity, microbial activity (Couic et al, 2018; Schimann et al, 2007; Velásquez Ramírez et al, 2021) and aggregate stability (Peláez et al, 2013). Plantings of leguminous trees can also increase soil biomass and microbial activity (dos Santos et al, 2013), although their impact may be higher in clay‐based soils than in sandier ones (Schimann et al, 2007).…”
Section: Restoration and Rehabilitation Of Gold‐mining Sites In The T...mentioning
confidence: 99%